2011
DOI: 10.1039/c0py00249f
|View full text |Cite
|
Sign up to set email alerts
|

Pd-mediated carbenepolymerisation: activity of palladium(ii) versus low-valent palladium

Abstract: Copolymerisation of olefins and carbene monomers was attempted with several well-defined Pd catalysts active in both olefin polymerisation and carbene polymerisation. In none of the attempts copolymer formation or even formation of the homopolymers was observed. This indicates that olefin polymerisation and carbene polymerisation are incompatible, despite the fact that the proposed transition states for these processes are very similar. Detailed investigations of Pd catalysed homopolymerisation of carbenes usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 57 publications
0
35
0
Order By: Relevance
“…22 Besides, the observation that the stereoregular PCEC show higher polymerization degree than atactic PCEC and they have different spectroscopic patterns point to the presence of different active species, differing in their chain-propagation behavior. 9 The increased steric hindrance of the polyimidazole ligands on the palladium centre could affect the carbene Scheme 2 Proposed chain-initiation, chain-transfer and chaintermination mechanisms for poly(imidazole-Pd)-mediated carbene polymerization.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…22 Besides, the observation that the stereoregular PCEC show higher polymerization degree than atactic PCEC and they have different spectroscopic patterns point to the presence of different active species, differing in their chain-propagation behavior. 9 The increased steric hindrance of the polyimidazole ligands on the palladium centre could affect the carbene Scheme 2 Proposed chain-initiation, chain-transfer and chaintermination mechanisms for poly(imidazole-Pd)-mediated carbene polymerization.…”
Section: Resultsmentioning
confidence: 99%
“…While Ihara and coworkers proposed the in situ generated Pd II -alkyl species as the active species, 3 de Bruin and coworkers supposed the involvement of low-valent Pd species (Pd 0 or Pd I ). 9 Even though the NMR spectra of the atactic polycarbenes suggests a radical polymerization mechanism, the involvement of free radical species was excluded. 9 Thus, the exact nature of the active intermediate is still unclear and so far, the mechanisms of the chain initiation and termination processes have been poorly understood, which require more investigations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous attempts to achieve these copolymerisations with Pd catalysts proved to be unsuccessful, due to clear differences in the nature of the active species responsible for both homopolymerisation reactions. 42 We decided to study these copolymerisations in more detail in the presence of Rh as a catalyst due to the activity of Rh towards both the polymerisation of functionalised carbenes (vide supra) as well as ethene polymerisation. [54][55][56] We anticipated that these two processes are potentially compatible, since ethene polymerisation is catalysed by Rh III complexes 55,56 and recently we demonstrated that the active species for carbene polymerisation is based on Rh III as well.…”
Section: Dalton Transactions Papermentioning
confidence: 99%
“…C1 monomers) as 'functional-group carriers' in coordinationinsertion polymerisation has proven to be successful, especially if densely functionalised, highly stereoregular polymers are desired. [29][30][31][32][33][34][35][36][37][38][39][40][41][42] Highly stereospecific (co)polymerisation of diazoesters (N 2 CHCOOR) can be achieved in good yields and with high M w in a Rh catalysed process. 30,[43][44][45][46][47][48][49][50][51] This leads to the formation of syndiotactic polymers bearing an ester functionality at every single carbon atom of the polymer main chain.…”
Section: Introductionmentioning
confidence: 99%